Children staying in hospital: a research on psychological stress of caregivers - Commodari Elena (BMC, 2010)
Abstract Background Having a child hospitalized is a stressful event for parents. Previous studies have found increased stress in families with children affected by different kinds of pathologies, and analyzed disease related objective variables producing stress. However, most of these studies recruited caregivers of children with chronic or serious illnesses, and focused on evaluation of objective environmental stressors and did not consider subjective "perception" of stress. The aim of this study was to investigate perception of acute stress in caregivers taking care of children without serious physical damage that were hospitalized for short periods. Moreover, some variables, such as recreational and school services offered to children, influencing perception of cognitive, physiological and behavioral state relating to the sensation of "being stressed" were analyzed. Methods This study was realized with a sample of caregivers of children hospitalized for mild acute diseases. Research was conducted using two standardized tests, PSM (Psychological Stress Measure) and STAI (State Trait Anxiety Inventory), whose characteristics of reliability and validity had been successfully established. Results Present data showed that caregivers of hospitalized children perceived high levels of stress and anxiety. Perception of stress was influenced by the degree of kindred with patients, length of hospitalization, and, notably, participation in some of the activities offered to children, mainly school services. Discussion Findings showed that child hospitalization is a stressful event for caregivers, even if hospitalization is for middle and transient pathologies. Perception of stress was influenced by length of hospitalization, and by degree of kindred. Findings even suggest that some services offered to children can modulate caregivers' perception of stress and impact of hospitalization. Caregivers whose children used school services describe themselves as less irritable and with higher emotional control compared to other caregivers. Considering the importance of education in a child's life, the possibility to continue school activities helped caregivers to feel less under pressure. In the light of this finding, amelioration of scholastic activities in pediatric departments may represent a critical point in order to provide a more agreeable hospital stay for children and their caregivers and, as a consequence, improve family involvement in care management.